Measurement of Process Capability of Manufacturing Process of Levetiracetam by Applying Concept of Six Sigma - Chandarana, Chandni; Rai, Pratiksha; Jadhav, Divya (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: A process capacity study is a study that uses capability indices to compare the output of an in-control process to specification constraints. Cp, Cpk, Ppk, and Pp are some of the statistics that can be used to assess process capability. The goal of the six-sigma study of levetiracetam tablets is to enhance and adjust the process to produce defect-free tablets and to maximize customer satisfaction. Process capability guarantees that procedures meet industry firm specifications while lowering process variation, which is essential for obtaining product quality characteristics. Before the batch is commercialized, this capacity research should be used in the industry. It is a cost-effective strategy that can shorten the inspection process. Materials and Methods: The control and capabilities of Antiepileptic tablets are described in this study. The research focuses on data collecting and analysis of process capability utilizing statistical software such as MINITAB 19.1. Results: The results of process capabilities for all the processes like hardness test, thickness test, disintegration test, loss on drying and friability tests were found to be above 1.33. Conclusion: The existing capability of the process is judged to be capable in this research.
Keywords: DMAIC phases; Epilepsy disorder; Levetiracetam; Process capability index; Six sigma process